CYBERSECURITY RISKS IN EDUCATIONAL COMMUNICATION SYSTEMS: ACCOUNT COMPROMISE, SOCIAL ENGINEERING, AND FINANCIAL FRAUD - Nematova Mohigul Bakhtiyor kizi (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
The rapid digitalization of education has improved communication, accessibility, and instructional efficiency. At the same time, it has exposed educational institutions to growing cybersecurity risks, especially those related to phishing, account compromise, social engineering, and financial fraud. Human factors remain central in many cyber incidents, making students and teachers particularly vulnerable in trust-based communication environments. This article examines major cybersecurity threats affecting educational communication systems, with special attention to compromised teacher accounts used to deceive students. It also discusses the causes and consequences of such attacks and proposes preventive measures based on international cybersecurity guidance and current research.